Description of two new Calicnemia from Vietnam and central Laos with notes on their congeners in Vietnam (Odonata: Platycnemididae) - Phan, Quoc Toan; Kompier, Tom; Karube, Haruki (Zootaxa, 2017)
Descriptions are given of two new species of Calicnemia: C. akahara sp. nov. from central and southern Vietnam and C. hamata sp. nov. from central Laos. C. soccifera Yu & Chen, 2013, and C. haksik Wilson & Reels, 2003, are recorded for the first time from Vietnam; C. uenoi Asahina, 1997, is redescribed with new illustrations provided of its anal appendages and genital ligula; and the occurrence of C. mortoni (Laidlaw, 1917) in Vietnam is discussed.